Magic : a novel - Steel, Danielle (New York : Random House Large Print, 2016)
The White Dinner is a love poem to friendship, joy, elegance, and the monuments of Paris. And each year it is an unforgettable summer night, especially for Jean- Philippe Dumas, a longtime participant, and the three couples he's carefully selected to attend this exclusive and cherished event. Interweaving the stories of seven individuals, lives will be forever changed on the eve of one such White Dinner; a night that will lead to new friendships, new love
Keywords: Couples -- Fiction; Interpersonal relations -- Fiction; Large type books. 15 MaineCat libraries have this item Copies Library Shelving Location Call Number and Serial Holdings Request Status Auburn Public Library Auburn PL New Large Type LARGE TYPE FIC Steel, D. DUE 09-27-16 Bangor Public Library Bangor Pub. Lib. New Arrivals LARGE TYPE S8128 .mag c.3 DUE 09-30-16 Baxter Mem Lib (Gorham) Baxter ML LP. Fiction LTE F Ste 1 HOLD Boothbay Hbr PL Boothbay Hbr Lg Print Fic LP FIC STE DUE 09-30-16 Camden Public Library Camden PL New Large Print LP F Ste AVAILABLE Curtis Mem Lib (Brunswick) CML Large Print Fic NEW LP FIC Steel D DUE 09-30-16 Edythe Dyer Comm Lib (Hampden) Edythe Dyer Large Type LT Fic Steel D DUE 09-29-16 Lewiston Public Library LewPL New Books LP F Steel,D DUE 09-28-16 McArthur PL (Biddeford) McArthur PL Adult Room Display LP Fic STEEL IN TRANSIT Paris Public Library Paris Large Print Large Print F Ste DUE 10-05-16 Portland PL Main Adult New Large Print STEEL Large Print Coll. DUE 10-19-16 Rockland Public Library Rockland PL Lg. Print Fic LP FIC STEEL DUE 09-28-16 Scarborough Public Library Scarborough PL New Large Type LARGE TYPE FIC STEEL PBK DUE 09-23-16 +1 HOLD So Portland PL - Main Library South Portland Main Lg Type NEW LTE DUE 09-20-16 Topsham Public Library Topsham PL Lg Print Fic LP FIC STE DUE 09-30-16